Pengaruh Keputusan Investasi, Keputusan Pendanaan, Kebijakan Dividen dan Profitabilitas Terhadap Nilai Perusahaan di BEI - Kalsum, Ummi; Oktavia, Yesi (Jurnal Ilmu Manajemen, 2021)
This study aims to determine the effect of investment decisions (PER), funding decisions (DER), dividend policy (DPR), and profitability (ROE) simultaneously and partially on the firm value on the IDX. The period used in this research is 5 years, starting from 2011-2015. Samples were taken using the purposive sampling method. The population in this study are all property, real estate, and building construction companies that have been and are still listed on the IDX for the 2011-2015 period. From a population of 60 property, real estate, and building construction companies, 33 companies were selected as samples. Data were analyzed using multiple linear regression analysis. Based on the results of data analysis, it is concluded that there is a significant influence on investment decisions, funding decisions, dividend policies, and profitability simultaneously on company value on the Indonesia Stock Exchange. There is a significant effect of investment decisions, funding decisions, dividend policies, and profitability partially on company value on the Indonesia Stock Exchange. Future studies should use more proxies that can be used for each variable.